Deviation From the common Style of Writing in contemporary Kurdish poetry/Poetry after the Uprising (1991-2003) as a sample.‌It's a Stylistics - Kamaran Aba-bakr Khudhur; Salim Radhid Salih (Zanco Journal of Humanity Sciences)
Language is the main pillar of Stylistic, and one of these principles is deviation from the rules and constitution of the language. According to most stylistic poets, deviation is the main basis of poetry, which distinguishes the poetic text from normal and daily expression. This is because using language is different from each other, This study is an attempt to show a kind of deviation from the common style of writing in Kurdish poetry after the uprising.